OITO NOVOS GÃŠNEROS DE PHANEROPTERINAE DO BRASIL (Orthoptera-Tettigoniidae) - Piza Jr., S. de Toledo (REVISTA DE AGRICULTURA, 2020)
OITO NOVOS GÃŠNEROS DE PHANEROPTERINAE DO BRASIL (Orthoptera-Tettigoniidae)